2016
DOI: 10.1186/s40623-016-0397-1
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal dependence on the frequency of Pi2 pulsations near the plasmapause using THEMIS satellites and Asian-Oceanian SuperDARN radars

Abstract: We herein describe a harmonic Pi2 wave that started at 09:12 UT on August 19, 2010, with data that were obtained simultaneously at 19:00-20:00 MLT by three mid-latitude Asian-Oceanian Super Dual Auroral Radar Network (SuperDARN) radars (Unwin, Tiger, and Hokkaido radars), three Time History of Events and Macroscale Interactions during Substorms (THEMIS) satellites (THEMIS A, THEMIS D, and THEMIS E), and ground-based magnetometers at low and high latitudes. All THEMIS satellites, which were located in the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In a pair of papers, Teramoto et al (2014Teramoto et al ( , 2016 presented two further case studies of Pi2 pulsations using data from the THEMIS mode. In the first (Teramoto et al 2014), a Pi2 wave was observed by HOK in the ground/ sea scatter, which was reflected via the ionospheric F region, as well as from a sporadic E layer.…”
Section: Pi2 and Pi1 Pulsationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a pair of papers, Teramoto et al (2014Teramoto et al ( , 2016 presented two further case studies of Pi2 pulsations using data from the THEMIS mode. In the first (Teramoto et al 2014), a Pi2 wave was observed by HOK in the ground/ sea scatter, which was reflected via the ionospheric F region, as well as from a sporadic E layer.…”
Section: Pi2 and Pi1 Pulsationsmentioning
confidence: 99%
“…The authors suggested that the concept of a pure cavity mode is not sufficient to explain the radar and coincident magnetometer observations and that a contribution from an Alfven mode must be considered in order to explain the observations. In a second study, Teramoto et al (2016) presented observations from three radars, HOK, TIG, and UNW, together with ground magnetometer data and electric and magnetic field observations by the THEMIS A, D, and E spacecraft. Note that, to date, this represents the only study of MHD waves at any latitude which use radar data from the two hemispheres.…”
Section: Pi2 and Pi1 Pulsationsmentioning
confidence: 99%
“…Most highlatitude Pi2 pulsations are believed to be caused by Alfvén waves associated with the transient response of the substorm current wedge [Baumjohann and Glassmeier, 1984], while low-latitude Pi2s are often attributed to cavity mode resonance [Saito and Matsushita, 1968;Kivelson and Southwood, 1985]. An outstanding open question concerns the generation mechanisms of Pi2s at midlatitudes, especially pulsations observed near the plasmapause, where there is a marked transition between high-and low-latitude Pi2 pulsations [Teramoto et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Coordinated observation of the phenomena by multiple satellites, (e.g., the THEMIS mission, Van Allen Probes, and the Magnetospheric Multiscale (MMS) mission) and ground facilities should be promoted to further enhance the groundwork of our project (Fujimoto et al 2012;Teramoto et al 2016 MN works for the MGF data evaluation and analysis. AF works for the initial MGF planning, hardware design and data analysis.…”
mentioning
confidence: 99%